(untitled) (Law and world, 2021)
The purpose of this article is to show the narrow boundaries and incompleteness of the Georgian legislation regarding rape, which fails to cover all the actions from which the protection of an individual"s negative sexual freedom is the responsibility of the state. The article aims to show the reader the advantages of the new approach in parallel with the critique of the old law regarding rape, which means expanding the scope of the definition of rape and hence criminalizing more actions. For this purpose, the importance of non-consent as the main element of the rape actus reus is discussed. The article also analyzes the importance of protecting the boundaries of rape so that the state does not unjustifiably restrict a person"s positive sexual freedom while protecting negative sexual autonomy. The purpose of this article is neither to criticize nor support any of the consent-based rape models ("no means no" or "only yes means yes" models), but rather to highlight the importance of consent to sex crimes and to emphasize the basic guideline for consent.